PENINGKATAN LITERASI MATEMATIS PESERTA DIDIK SMP NEGERI 5 SERUWAY MELALUI MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) - Rina Andreyanti; Saiman Saiman (UJMES (Uninus Journal of Mathematics Education and Science), 2023)
Research. It's purposeful. to be able to know. the existence of increasing the mathematical literacy of students in grades VII-1 of SMP Negeri 5 Seruway after experiencing learning using the Missouri Mathematics Project (MMP) learning model. The design in this study One-Group Pretest-Posttest Design. The research sample used was students in grades VII-1 of junior high school. Land 5 Seruway. The technique.. used to collect data, namely pre-test and post-test.Based on the results of hypothesis testing,  =2,048 and =36.7 were obtained, so that  (36.7 2,048) with a significant level of 5% so that  not rejected and rejected, this means that there is an increase in the mathematical literacy of students after experiencing learning using the MMP learning model at SMP Negeri 5 Seruway.